2013
DOI: 10.1002/ppap.201300072
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Vegetative Microorganisms and Bacillus atrophaeus Endospores by Reactive Nitrogen Species (RNS)

Abstract: Plasma is used as a common technology for the treatment and modification of surfaces in a variety of industrial branches. Decontamination of inorganic materials by plasma is possible with deterioration of the materials properties of a few nanometres. The inactivation efficacy of microwave plasma processed air against vegetative bacteria and bacterial endospores was investigated. The gained results provide inactivation rates up to 6 log in total treatment times (15–30 min) comparable to sterilization treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…The microwave driven plasma system used in this study generates NO 2 in high concentrations which is visible as a brown gas inside the glass bottles and has been identified as the predominant species using MS in previous studies . The colour dissipates within minutes of storage time in closed containers indicating dissolution of NO 2 into the liquid and/or further reactions.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…The microwave driven plasma system used in this study generates NO 2 in high concentrations which is visible as a brown gas inside the glass bottles and has been identified as the predominant species using MS in previous studies . The colour dissipates within minutes of storage time in closed containers indicating dissolution of NO 2 into the liquid and/or further reactions.…”
Section: Resultsmentioning
confidence: 77%
“…Work by Lukes and co‐workers has demonstrated the pH dependent reaction of H 2 O 2 and nitrite to form peroxynitrite, a reaction which could be a cause for the absence of detectable H 2 O 2 in PTW‐MW and undetectable levels of nitrite in PTW‐DBD. However, previous studies detected no O • , O 2 • , OH • or O 3 and indicated a lack of ROS generated by the MW plasma device due to high gas temperatures in the centre of the plasma . For the DBD device which generates high concentrations of H 2 O 2 , a reaction with nitrite during/directly post discharge is possible and could have resulted in the formation of the detected NO 3 − .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations